The influence of the wrestling technique on contact efficiency of young male team handball players - Foretic, N.; Karnincic, H.; Uljevic, O. (Archives of Budo, 2011)
Background and study aim: The purpose of this study was to determine the impact of learning of some wrestling techniques on the efficiency in a contact game. Material/Methods: The research was conducted on a sample of 20 handball players (10-12 years). Experimental and control group rated the effectiveness in contact play before and after the treatment. The treatment consisted of learning and practicing five wrestling techniques applied on the preparation part of the training session. Results: Initial testing did not show statistically significant differences in efficiency between groups in defense and in attack. Results of the final testing showed that statistically significant differences between the experimental (defense p=0.04, attack p=0.02) and control group (defense p<0.01, attack p=0.03). Analysis of differences between groups show that the experimental group achieved statistically significant (p<0.01) better results in defense and attack performance. Conclusion: The research has shown that teaching young handball players wrestling techniques can significantly improve their performance.